Linear groups saturated by subgroups of finite central dimension - Semko, N.N.; Skaskiv, L.V.; Yarovaya, O.A. (Доповіді НАН України, 2019)
Let F be a field, A be a vector space over F, and G be a subgroup of GL(F, A). We say that G has a dense family of subgroups having finite central dimension, if, for every pair of subgroups H, K of G such that H ≤ K and H is not maximal in K, there exists a subgroup L of finite central dimension such that H ≤ L ≤ K (we can note that L can match with one of the subgroups H or K). We study locally solvable linear groups with a dense family of subgroups having finite central dimension. Нехай F – поле, A – векторний простір над F, G — підгрупа GL(F, A). Будемо говорити, що G має щільне сімейство підгруп, які мають скінченну центральну розмірність, якщо для кожної пари підгруп H, K з G такої, що H ≤ K і H немаксимальна в K, існує така підгрупа L скінченної центральної розмірності, що H ≤ L ≤ K (зазначимо, що L може збігатися з однією з підгруп H або K). У роботі описані локально розв’язні лінійні групи з щільним сімейством підгруп, що мають скінченну центральну розмірність. Пусть F — поле, A — векторное пространство над F, G — подгруппа GL(F, A). Будем говорить, что G имеет плотное семейство подгрупп, имеющих конечную центральную размерность, если для каждой пары подгрупп H, K из G такой, что H ≤ K и H немаксимальная в K, существует такая подгруппа L конечной центральной размерности, что H ≤ L ≤ K (отметим, что L может совпадать с одной из подгрупп H или K). В работе описаны локально разрешимые линейные группы с плотным семейством подгрупп, имеющих конечную центральную размерность.